An analysis of current and future electricity production from biogas in Germany - Balussou, David (Produktion und Energie, 2023)
In this work a process simulation model identifies the most profitable German biogas plant types and sizes. Small manure and large-scale biowaste plants are currently the most economically attractive installations whereas the valorization of energy crops turns out to be unprofitable. Future developments are assessed with the help of a regional optimization model under constraints. Capacity expansion concerns small-scale manure and biowaste installations rather than plants based on energy crops.